ANALISIS KELAYAKAN TEKNIS DAN FINANSIAL DARI INVESTASI PENGADAAN TRAY DRYER BERBAHAN BAKAR BIOMASSA PADA USAHA ARANG TEMPURUNG KELAPA BERBASIS EKSPOR (Studi Kasus di Tropica Nucifera Industry – Yogyakarta) - Fanny Widadie; Dimas Rahadian Aji M; Nur Heriyadi Parnanto (Agriekonomika, 2013)
The purpose of the study is to assess the technical and financial feasibility of procurement investment Tray Dryer fueled biomass to operations of coconut shell charcoal briquette in PT. Tropica Nucifera Industry. The result showed that investment-Tray Dryer on cocnut shell charcoal briquette bussiness was highly feasibile both the technical and financial aspects. The technical aspect was seen that the quantity-production capabilities of coconut shell charcoal briquettes using a dryer-Tray Dryer could be increased 15 percent compared the previous consdition-used of solar energy. While the quality of the charcoal briquettes produced from Tray Dryer was a much butter quality, moisture content (6.39%); ash (2.65%); carbon-bound (85.83%), compared to using sunlight, water content (15.89); ash (2.57%) and carbon-bound (77.32%).The financial aspects of procurement Tray Dryer investment that its value was more feasible than previous, nothing Tray Dryer. Coconut shell charcoal briquet enterprises without using Tray Dryer was feasible to be done with NPV 1,058,928.12, IRR 63%, Payback Period 1 year and 9 moths, Net B/C 2.25 and analysis of swicthcing value reached 20 percent. And after the business using Tray Drayer, the financial analysis was much more feasible with NPV 2,285,500,498.12, IRR 113%, Payback Period 11 months, Net B/C 3.5 and analysis of switching value reached 50 percent.